2018
DOI: 10.1111/pace.13271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remote ischemic preconditioning on left atrial remodeling and prothrombotic response after radiofrequency catheter ablation for atrial fibrillation

Abstract: RIPC before RFCA for paroxysmal AF significantly reduces the increase in markers of left atrial remodeling and endothelial damage associated with the procedure, and results in a lower ERAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…observed that AF recurrence in the 3 months after the PAF ablation was signi cantly lower in the RIC group than in the control group. The RIPC group also showed a lower increase in atrial remodeling marker Matrix Metalloproteinase-9 and endothelial dysfunction marker von Willebrand-factor in blood samples compared with the control group 30 . Our study has shown that HRV was improved in heart failure patients by CRIC, which was a marker of autonomic nervous stress 19 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…observed that AF recurrence in the 3 months after the PAF ablation was signi cantly lower in the RIC group than in the control group. The RIPC group also showed a lower increase in atrial remodeling marker Matrix Metalloproteinase-9 and endothelial dysfunction marker von Willebrand-factor in blood samples compared with the control group 30 . Our study has shown that HRV was improved in heart failure patients by CRIC, which was a marker of autonomic nervous stress 19 .…”
Section: Discussionmentioning
confidence: 85%
“…Kosiuk et al17 demonstrated that 3 sessions of RIC reduced the inducibility (23.3% vs 46.6%, p = 0.003) and sustainability (15.1% vs 32.9%, p = 0.01) of PAF signi cantly, which was possibly mediated by decrease in dispersion of atrial refractory periods (16.0 ± 14.0 ms vs 22.7 ± 19.0 ms, p = 0.21) and reduction in atrial conduction delay. Han et al30…”
mentioning
confidence: 99%
“…Kosiuk,et al 17) demonstrated that three sessions of RIC significantly reduced the inducibility (23.3% versus 46.6%, P = 0.003) and sustainability (15.1% versus 32.9%, P = 0.01) of PAF, which was possibly mediated by a decrease in dispersion of atrial refractory periods (16.0 ± 14.0 millisecond versus 22.7 ± 19.0 millisecond, P = 0.21) and reduction in atrial conduction delay. Han, et al 30) observed that AF recurrence 3 months after the PAF ablation was significantly lower in the RIC group than in the control group. The RIPC group also showed a lower increase in atrial remodeling marker matrix metalloproteinase-9 and endothelial dysfunction marker von Willebrand factor in blood samples compared with the control group.…”
Section: Discussionmentioning
confidence: 98%
“…e results obtained using these methods showed good detection performance. e classification accuracy, sensitivity, and specificity of the SVM and RBF have been found to be high, thus making it a good option for the diagnosis [75].…”
Section: Discussionmentioning
confidence: 99%